2009
DOI: 10.4103/0970-2113.53232
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria of tuberculous sarcoidosis

Abstract: With the object to strengthen the clinical status of tuberculous sarcoidosis, we present in this article, the case records published in internationally recognized journals by specialists. From review of clinical material, we have also formulated a table that defines diagnostic criteria of tuberculous sarcoidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Also, in a study done by Kumar et al 10 the most common presenting symptom was found to be cough, which was present in 131 (89.7%) patients, followed by exertional dyspnea in 102 (69.9%). These observations are also in accordance with other Indian studies 18,19 and with ATS statement on sarcoidosis. 5 In this study constitutional symptoms (fever, anorexia, and weight loss) found in12 (21.4%) patients of sarcoidosis.…”
Section: Resultssupporting
confidence: 93%
“…Also, in a study done by Kumar et al 10 the most common presenting symptom was found to be cough, which was present in 131 (89.7%) patients, followed by exertional dyspnea in 102 (69.9%). These observations are also in accordance with other Indian studies 18,19 and with ATS statement on sarcoidosis. 5 In this study constitutional symptoms (fever, anorexia, and weight loss) found in12 (21.4%) patients of sarcoidosis.…”
Section: Resultssupporting
confidence: 93%
“…So when they coexist, it remains a challenging task to diagnose them individually and treat accordingly. Coexistence of both these entities has sometimes been referred to as tuberculous sarcoidosis 5. It shows mainly three patterns (1) patients who have TB subsequently develop sarcoidosis, (2) patients develop concomitant sarcoidosis and TB; and (3) patients with chronic sarcoidosis develop TB due to treatment-related immunity suppression 5…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis, it was suggested that there is association between mycobacterium (both Mycobacterium tuberculosis complex and nontuberculous) and sarcoidosis (9). Sarcoidosis occasionally develops in patients previously treated for tuberculosis (3,6,10). Less commonly, TB develops as an opportunistic infection in patients following corticosteroid treatment for sarcoidosis (5).…”
Section: Figure 4: Follow-up Chest X-ray After Antituberculosis Treatmentioning
confidence: 99%
“…Less commonly, TB develops as an opportunistic infection in patients following corticosteroid treatment for sarcoidosis (5). Coexistence of TB and sarcoidosis is rare (2)(3)(4)(5). Clinical and radiological features of TB and sarcoidosis overlap quite a bit and therefore, diagnostic dilemma often persists.…”
Section: Figure 4: Follow-up Chest X-ray After Antituberculosis Treatmentioning
confidence: 99%